ESR-Study of the Proton Exchange with Aliphatic Amino Acids in Toluene - Stadnik, I.L.; Abilkanova, F.Zh.; Kudryavtseva, Ye.V.; Nikolskiy, S.N.; Masalimov, A.S. (Bulletin of the University of Karaganda – Chemistry, 2022)
This paper presents the results of an ESR spectroscopic study of the intermolecular proton exchange kinetics with some isomers of aminocaproic acid, such as 2-aminohexanoic and 6-aminohexanoic acids in the toluene indifferent medium. A stable semiquinone radical, namely 3,6-di-tert-butyl-2-hydroxyphenoxyl, is used as a spin probe. The ESR spectra have been recorded on a RE-1306 spectrometer. The article provides the ob-tained dynamic spectra of the intermolecular proton exchange process. Modeling of the proton exchange ESR spectra has been carried out using a previously developed program, which is based on a four-jump model of this reaction and modified Bloch equations. The kinetic parameters of the process of acid-base interaction of the spin probe with amino acids and the activation barrier of the reaction have been estimated with a mini-mum error based on a comparison of the model spectra with the experimental ones. The obtained data have been analyzed and compared with previous studies. It has been found that the reaction rate of the intermo-lecular proton exchange between 3,6-di-tert-butyl-2-hydroxyphenoxy and studied aliphatic amino acids is comparable to the same with aliphatic carboxylic acids. Hoewever, in our case, there is an increase in the ac-tivation barrier, which apparently is associated with a negative effect on the intramolecular hydrogen bonding process between the amino and the carboxyl groups in the amino acid molecule
Keywords: ESR-spectroscopy; proton exchange reactions; spin probe; semiquinone radical; Bloch equation; aminohexanoic acid; 3,6-di-tert-butyl-2-hydroxyphenoxyl; OH-acids